The Industrial Base for Carbon Dioxide Storage - Ortiz, David S. (RAND Corporation, 2013)
If policies aimed at large reductions of carbon dioxide (CO2) emissions are enacted, more carbon capture and storage will be needed. RAND researchers explored the ability of the industrial base supporting the transportation and sequestration of CO2 to expand, assessing the industrial base for transportation and injection of CO2 for both geologic storage and enhanced oil recovery.